Saving the Other: War and Peace in Emmanuel Levinas’s Philosophy - Saldukaitytė, Jolanta (Religija ir kultūra, 2016)
[full article and abstract in Lithuanian; abstract in English]The present article discusses the topics of war and peace in the philosophy of Emmanuel Levinas. It focuses on Totality and Infinity(1961) and aims to show that war here is presented as a suspension of morality. This article argues that on the one hand, war is understood as a historical event, and as an ontological principal on the other. In turn, peace is also understood ambiguously: first, as an opposition to war, and second, as an eschatology which is the true peace. The question of war and peace also reveals the problematic relationship between politics and ethics in Levinas’s philosophy. These themes penetrate and frame the book. And, as totality is war and infinity is peace, the alternative title of Totality and Infinity might be War and Peace.
Keywords: Levinas; war; peace; morality; ethics; politics